The improvement of Academic Commitment through Mentoring and Service-Learning - Hervás-Torres, Mirian (2022)
Introduction. Higher education institutions constantly face challenges to improve their productivity, competitiveness, social impact, quality of education, and training delivered to students. Two of the responses to improve the quality of education and training offered to students and the social impact are service-learning and mentoring. The merit of both teaching interventions is that they allow a more effective connection between the curriculum, the social needs, and the professional world outside. Objective. This investigation aimed to explore the effectiveness of the Huelva Educa Program (HEP) to improve the level of academic commitment of participating students as mentors. Method. The sample comprised 54 students from the University of Huelva, selected through a sampling non-probability convenience. A quasi-experimental pretest-postest design involving undergraduate students was adopted, where the dependent variable was measured by the Questionnaire on the academic commitment of the university students and the HEP mentors’ workbook. Results. Self-reported results show that students have significantly increased behaviors related to participation in class, analyses of experiences and ideas, reflective analyses of experiences and ideas, critical reasoning, and tasks in a foreign language, among others. Conclusions. This work provides evidence on the program’s effectiveness for improving the preparation of their subjects, increasing academic achievement, or increasing their active and collaborative learning, recommending the importance of adopting this type of program.